Efektivitas Dan Kontribusi Sumber-Sumber Pendapatan Asli Daerah Di Satuan Wilayah Pengembangan Malang Raya - Roseida Cantika; Wahyu Hidayat Riyanto (Jurnal Ilmu Ekonomi, 2023)
The purpose of this study was to find out how much the level of effectiveness and contribution obtained from the sources of Regional Original Revenue (PAD). This research was conducted in the Greater Malang Development Area Unit (SWP), which consists of Malang Regency, Malang City, and Batu City. The data used is secondary data, namely data taken from official data from the Directorate General of Fiscal Balance (DJPK Ministry of Finance). The data used includes target data and realization of PAD, regional taxes, regional levies, separated regional wealth management results, and other legitimate PAD. The research method used is the ratio of effectiveness and contribution of PAD sources to PAD in the three regions used. The results show that the average level of effectiveness of PAD in Malang Regency, Malang City, and Batu City in 2021 is 103%, 92%, and 93%, respectively, which are classified as effective criteria. In this way it can be concluded that the performance of the government in SWP Malang Raya (Malang Regency, Malang City, and Batu City) has been able to realize the regional PAD effectively and exceed the targets set.